2014
DOI: 10.1038/ncomms6407
|View full text |Cite
|
Sign up to set email alerts
|

Progressive contraction of the latent HIV reservoir around a core of less-differentiated CD4+ memory T Cells

Abstract: In patients who are receiving prolonged antiretroviral treatment (ART), HIV can persist within a small pool of long-lived resting memory CD4+ T cells infected with integrated latent virus. This latent reservoir involves distinct memory subsets. Here we provide results that suggest a progressive reduction of the size of the blood latent reservoir around a core of less-differentiated memory subsets (central memory and stem cell-like memory (TSCM) CD4+ T cells). This process appears to be driven by the difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
127
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(133 citation statements)
references
References 27 publications
6
127
0
Order By: Relevance
“…This view is supported by data from two long-term gene therapy clinical trials demonstrating that these T memory stem cells are able to persist and preserve their precursor potential for up to 12 years, consistent with the critical role of these cells for maintaining lifelong pathogen-specific immune defense (24). Moreover, CD4 T SCM cells have recently been shown to provide an important cellular source of HIV-1 long-term persistence, further supporting the role of T SCM cells as extremely long-lasting memory cells (31,32). Although HIV-1-specific T cells can influence HIV-1 disease progression in untreated patients to some extent (33), numerous studies suggest that these cells are disturbed and dysfunctional during progressive disease (12,13,(34)(35)(36).…”
Section: Discussionmentioning
confidence: 58%
“…This view is supported by data from two long-term gene therapy clinical trials demonstrating that these T memory stem cells are able to persist and preserve their precursor potential for up to 12 years, consistent with the critical role of these cells for maintaining lifelong pathogen-specific immune defense (24). Moreover, CD4 T SCM cells have recently been shown to provide an important cellular source of HIV-1 long-term persistence, further supporting the role of T SCM cells as extremely long-lasting memory cells (31,32). Although HIV-1-specific T cells can influence HIV-1 disease progression in untreated patients to some extent (33), numerous studies suggest that these cells are disturbed and dysfunctional during progressive disease (12,13,(34)(35)(36).…”
Section: Discussionmentioning
confidence: 58%
“…HIV is currently incurable due to the presence of HIV integrated into the genome of resting cells, predominantly T CM , which constitute the major reservoir for HIV in patients on suppressive ART (36). In the setting of HIV reactivation from latency, the "shock and kill hypothesis" (37) predicts that HIV reactivation should cause reactivating cells to die.…”
Section: Apoptosis Resistance Of Cd4 Central Memory T Cells (T CM )mentioning
confidence: 99%
“…infected cells under ART increases over time (15)(16)(17). To investigate the potential role of CD4 ϩ T SCM as a source of virus persistence in SIV-infected RM, we measured the level of total cellassociated SIV DNA in the four main memory CD4 ϩ T cell subsets (T SCM , T CM , T TM , and T EM ) that were flow sorted from both peripheral blood and lymph nodes.…”
Section: Constitution Of Cd4mentioning
confidence: 99%
“…The observation of high levels of HIV DNA in CD4 ϩ T SCM from HIV-infected individuals under ART, together with particular biological properties of these cells, such as high in vivo longevity, relative quiescence, and marked proliferative potential, led to the hypothesis that these cells represent a crucial contributor to virus persistence despite their relative low frequency (15). Indeed, two recent studies demonstrated that the duration of ART is directly correlated with the relative contribution of CD4 ϩ T SCM to the HIV DNA reservoir in HIV-infected individuals (15,16).…”
mentioning
confidence: 99%